CD 99 expression is strongly associated with clinical outcome in children with B‐cell precursor acute lymphoblastic leukaemia - Chen, Dongfeng; Camponeschi, Alessandro; Wu, Qingqing; Gerasimcik, Natalija; Li, Huiqi; Shen, Xue; Tan, Yujie; Sjögren, Helene; Nordlund, Jessica; Lönnerholm, Gudmar; Abrahamsson, Jonas; Fogelstrand, Linda; et al. (British journal of haematology, 2019)
Our study aimed to determine the expression pattern and clinical relevance of CD 99 in paediatric B‐cell precursor acute lymphoblastic leukaemia ( BCP ‐ ALL ). Our findings demonstrate that high expression levels of CD 99 are mainly found in high‐risk BCP ‐ ALL , e.g. BCR ‐ ABL 1 and CRLF 2 Re/Hi , and that high CD 99 mRNA levels are strongly associated with a high frequency of relapse, high proportion of positive for minimal residual disease at day 29 and poor overall survival in paediatric cohorts, which indicate that CD 99 is a potential biomarker for BCP ‐ ALL .